APPRAISAL OF INTERNATIONAL CRIMINAL COURTS: LESSONS FOR THE GAMBIA ON JAMMEH’S ALLEGED CRIMES - Ousu Mendy (Penerbit Universitas Atma Jaya Yogyakarta, 2022)
This research is determined to present an appraisal of International Criminal Tribunal for Rwanda (hereinafter referred to as ICTR) from an international law perspective in their quest to serve justice after the perpetration of the heinous atrocities of genocide in 1994 in Rwanda and other criminal tribunals and courts. It examines the failure of the international community to intervene, the raison d’être of ICTR as the main tribunal in this research and its fate. It focuses on the national mechanisms and the need for The Gambia to achieve justice for victims of the former President, Yahya Jammeh by reflecting on Rwanda. These findings are used to gauge The Gambia’s Truth, Reconciliation and Reparations Commission’s (hereinafter referred to as the TRRC) recommendations and The Gambia’s white paper on Jammeh’s alleged crimes. It examines the violation of human rights, the prospects of this white paper and my perspective on possible mechanisms for social justice, integration and cohesion in The Gambia. This research, therefore, finds out that a hybrid court led by The Gambia and supported by judges in Africa is quite relevant to dealing with these alleged crimes because it is established with the aim of addressing this issue of Jammeh’s alleged human rights violations. This is so when The Gambia liaises with the African Union and the Economic Community of West African States to strengthen this hybrid court by providing this court with judges of outstanding legal acumen in hearing cases of such.